Pengaruh Latihan Tendangan Menggunakan Kaki Dalam dan Punggung Kaki Penuh terhadap Ketepatan Shooting ke Gawang pada Pemain PS UNIMUDA Sorong - Musa Kambu; Waskito Suryo Aji Putro; Leo Pratama (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to determine the effect of shooting practice using the inside of the foot and full instep on shooting accuracy at the goal of PS Unimuda Sorong players. This study uses an experimental method with a